The Effect of Electromagnetic Current in the Plantlet in vitro in Cucumis sativus L. - Saadi, A. J. AL.; AL.Jibouri, A.j.; AL.Bassam, S. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Seeds of three American species of cucumber:-Lot number (EM285) signed as number 1, To CAEEN F1 signed as number 2 ,and Hybird Super Green F1 signed as number 3, were exposed to two kinds of physical effects .They were given :- 4 frequencies of the electric current (0,1,2and 2.5) Am for five minutes using electro- magnetic generator .Then the three species exposed to Ultra-Violet (UV)wave for four periods (0,30,60 and 90)sec. respectively at 254 nm using Hood light .After exposure time the seeds were planted in sterlized media(MS) with Benzyladenine (BA)and left in the incubator for2-3 weeks .Then ,plantlets of the three species were taken to study the root system ,shoot system ,dry and wet weight for them . The results showed that species 3 which was exposed to 2.5 Am for electric exposure and 90 sec. of UV had a significant increase compared with species 1 and 2.